1986
DOI: 10.1136/bmj.292.6522.721
|View full text |Cite
|
Sign up to set email alerts
|

Amodiaquine induced agranulocytosis and liver damage.

Abstract: Seven cases of agranulocytosis and two ofliver damage that were probably due to amodiaquine treatment were studied. In five cases agranulocytosis was combined with liver damage, and in one case of primary liver damage moderate neutropenia was present. Three patients died. High total doses or prolonged duration of treatment, or both, appear to favour the occurrence of these reactions.The clustering of five of the seven cases of agranulocytosis within six months in one medical centre indicates that the risk to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
153
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(155 citation statements)
references
References 7 publications
1
153
0
1
Order By: Relevance
“…Imported malaria, however, illustrates only a part of the problem, as even in short-term travelers an important proportion of cases is treated abroad and is not reported. Increasing distribution of chloroquine-resistant R jalciparum and growing concern about adverse reactions due to Fansidar [22,23] and amodiaquine [24,25] are likely to lead to diminished protection of the travelers visiting endemic areas and to a further increase in the incidence of malaria. A more-detailed analysis of the risk of malaria with respect to different types of prophylaxis has just been published [26].…”
Section: Methodsmentioning
confidence: 99%
“…Imported malaria, however, illustrates only a part of the problem, as even in short-term travelers an important proportion of cases is treated abroad and is not reported. Increasing distribution of chloroquine-resistant R jalciparum and growing concern about adverse reactions due to Fansidar [22,23] and amodiaquine [24,25] are likely to lead to diminished protection of the travelers visiting endemic areas and to a further increase in the incidence of malaria. A more-detailed analysis of the risk of malaria with respect to different types of prophylaxis has just been published [26].…”
Section: Methodsmentioning
confidence: 99%
“…Amodiaquinelinduced -hepatitis during malaria prophylaxis is well described and may be associated with neutropenia (LARREY et al, 1986;NEFTEL et al, 1986;WOODTLI et al, 1986;CHARMOT & GOUJON, 1987;BERNUAU et al, 1988;RAYMOND et al, 1989). These side-effects are thought to be immune mediated but the pathogenesis remains unclear (CLARKE et al, 1991).…”
mentioning
confidence: 99%
“…Clinically, reported cases have ranged from a mild, transient elevation of liver enzymes With few symptoms (LARREY et al, 1986;CHARMOT & GOUTON. 1987) NEFTEL et al, 1986), or death (NEFTEL et al, 1986;BEFWUAU et al, 1988;RAYMOND et al, 1989). …”
mentioning
confidence: 99%
“…It became therapeutically important with the widespread emergence of resistance to chloroquine, since strains of P. falciparum resistant to chloroquine were shown to remain sensitive to amodiaquine. However, in 1986 it was demonstrated that approximately 1 in 2000 subjects taking amodiaquine for malaria prophylaxis developed neutropenia or hepatoxicity or both [35,36]. Park and his colleagues have investigated the possible metabolic basis of this adverse drug reaction [37].…”
Section: Chemistry and Adverse Drug Reactionsmentioning
confidence: 99%